Development of automatic inserting chain/ring for keyholder - Muhammad Azam, Abang Affandi (2016)
This thesis presents the development of automatic inserting ring for a key holder. The proper calculation and simulation of every component of the machine are important to avoid the failure of the machine. The suitable force and mechanism is required in order to insert the ring to the key holder. The parameter of this project is the material properties and the diameter of the wire that will formed to ring shape. The design of the project must meet the condition to able to withstand the shear force in every components. The project is fabricate using FANUC CNC Milling machine.